2015
DOI: 10.1007/s40675-015-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Positive Airway Pressure Modalities

Abstract: Auto-adjusting positive airway pressure (PAP) devices are increasingly becoming the first line treatment for obstructive sleep apnea (OSA). More complex sleepdisordered breathing such as Cheyne-Stokes respirations and central sleep apnea related to heart failure as well as complex sleep-disordered breathing related to chronic hypoventilation syndromes may require the use of advanced positive airway pressure modalities such as automated servo ventilation (ASV) and volume targeted pressure limited ventilation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In addition, each CPAP device has different designs and methodologies. The treatment efficacy and patient adherence differ widely among CPAP devices (4). However, to our knowledge, the effects of CPAP devices on OSA control and comfort in Japanese patients have not been reported.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, each CPAP device has different designs and methodologies. The treatment efficacy and patient adherence differ widely among CPAP devices (4). However, to our knowledge, the effects of CPAP devices on OSA control and comfort in Japanese patients have not been reported.…”
Section: Introductionmentioning
confidence: 85%
“…Conversely, the device decreases the pressure until the flow limitation is detected while monitoring airway patency (4). The ResMed device uses forced oscillation of small pulses at 4 Hz and subsequent larger discrete test pulses to detect an open airway (4). The device also responds to flow limitation and apnea on a breath-by-breath basis (4).…”
Section: Cpap Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Academy of Sleep Medicine (AASM) recommends that HSAT only be used in patients with high pretest probability of moderate to severe disease without other significant medical or sleep related comorbidities under the guidance of a sleep specialist within a management pathway that uses PSG to confirm diagnosis when HSAT findings are inconclusive or negative [10]. Use of auto-titrating positive airway pressure (APAP) devices can also streamline management of OSA by obviating the need to perform attended PSG PAP titration in some OSA patients [11]. Studies have shown equivalent outcomes using APAP compared to manual PAP titration in appropriately selected patients; medically stable patients at high risk for moderate to severe OSA who do not have significant cardiorespiratory comorbidities [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%